INTEGRALAB: A S OFTWARE FOR FUNCTIONS' INTEGRATION AND SOLUTION OF DIFFERENTIAL EQUATIONS THROUGH NUMERICAL METHODS. - Ruiz Lizama, Edgar (2006)
This work presents the design and implementation of a software whose name is IntegraLAB, which can be used as a tool to solve functions' integration problems, and for the solution of ordinary differential equations through applying numerical methods. As for its results, the software has been tested taking functions whose results are known, and have been presented in literature about numerical methods, and then contrasted with those obtained or given back by IntegraLAB. Accuracy and exactness have been found according to the expected results.